Postoperative mastoid cavity problems: a tertiary care centre experience - Saraf, Aditiya; Ahmad, Raies; Jyoti, Deep; Kalsotra, Parmod (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aims and objectives of the study were to find incidence and causes for postoperative mastoid cavity problems after modified radical mastoidectomy. Methods: The present prospective study was conducted in the Department of ENT, SMGS Hospital, GMC Jammu from September 2017 to February 2020 on 25 patients with active squamosal chronic otitis media. All patients underwent modified radical mastoidectomy after taking written and informed consent. A period of 3 months postoperatively was taken as a healing time for complete epitheliasation of cavity. Any patient presenting with symptoms beyond this period was considered a cavity problem case. Results: Out of 25 patients, 9 patients had cavity problems, the incidence of cavity problem being 36%. Perforation in tympanic membrane was seen in 7 patients (77%) and high facial ridge in 2 patients (22%). There was no case of narrow meatoplasty in our study. Conclusions: Incidence of mastoid cavity problems can be reduced if the open cavity procedures are executed adequately.